Regeneration of As(V) loaded granular activated carbon through desorption in FeCl3, CaCl2 and MgCl2 aqueous solutions - Moed, Niels Michiel (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
As(V) adsorption on granular activated carbon (GAC) and subsequent desorption in dH2O was modeled using the pseudo-first and pseudo-second order kinetic models. Regeneration was achieved by immersing loaded GAC in NaCl, FeCl3, CaCl2 and MgCl2 aqueous solutions. As(V) detection after desorption was highest for NaCl but subsequent adsorption was lowest. Regeneration was highest in FeCl3 solution of pH 2 followed closely by pH 3, but As(V) precipitation appeared superior at pH 3. Molar ratios of Fe, Ca and Mg to As were tested in the range of 0.75:1 to 12:1 where a logarithmic relation was found between the molar ratio and As(V) desorption as diluted in HNO3 and H2O and subsequent adsorption. Precipitation was nearly complete in FeCl3, limited in MgCl2 at a ratio of 12:1 and not observed in CaCl2. While kinetic values were lower than in previous tests, the pseudo-first and pseudo-second order models could accurately describe desorption in CaCl2 and MgCl2 but not in FeCl3 due to precipitation. Desorption in FeCl3 was most effective in precipitating As(V), being highest at a molar ratio of 6:1, but regeneration was slightly higher at a molar ratio of 12:1